Report of the peer-to-peer exchange on NDCs development, implementation, and investment priorities among African countries - African Group Of Negotiators Experts (Agnes) Support; Bioversity International and International Center for Tropical Agriculture; International Livestock Research Institute (ILRI) (2025)
As countries advance through the iterative NDC cycle, the need for enhanced peer learning has become increasingly evident. Many African countries continue to reflect on lessons from NDC 2.0 implementation while simultaneously designing successive NDCs that are better aligned with their Long-Term Low Emission and Climate-Resilient Development Strategies (LT LEDS). Given that countries are at different stages of NDC preparation and implementation, structured peer exchange provides an essential mechanism for identifying what works, what does not, and the opportunities for strengthening ambition and implementation capacity.